(untitled) (Research, Society and Development, 2020)
The objective of this research was to evaluate the carcass characteristics and meat quality of male and female Lionhead rabbits. Twenty rabbits of both sexes were used, which constituted the treatments. The animals were fed with concentrated, roughage and water at will for 60 days. The animals were weighed weekly until the end of the feeding period, when they were then slaughtered. The adopted statistical design was completely randomized and the Tukey test was applied to evaluate the means. The animals did not show differences for live weight at slaughter (1,499kg); empty body weight (1.00kg); hot (0.798kg) and cold (0.791kg) carcass weight; hot (53.23%) and cold (52.78%) carcass yield. The females had liver weights (75.70g) and gastrointestinal tract (173.90g) higher than those observed in males that were 50.43g and 128.28g, respectively; however, no differences were found for heart, kidney and lung weight. No differences were observed for meat quality variables: pH 0h (6.77) and 24h post-slaughter (5.48); luminosity (49.86), red (4.70) and yellow (5.78); cooking losses (22.26%) and shear force (4.45kgf/cm²). Sex does not influence meat quality and carcass characteristics of Lionhead rabbits. Male and female Lionhead rabbits have potential for meat production purposes, as their carcass characteristics and meat quality make it favorable to trade in meat products.